Early osteoarthritis: development of diagnostic criteria - L. I. Alekseeva; K. A. Telyshev (Современная ревматология)
Early osteoarthritis (OA) is a poorly studied problem, the importance of which is due to both the prevalence of OA in the population and the high medical and economic costs of treatment and rehabilitation in patients with this disease. The accumulating data indicate that the earlier active management of patients with OA may lead to a better long-term prognosis; to date, however, the very formulation of the concept of «early osteoarthritis», as well as the holistic clinical diagnostic criteria of the disease, have not been fully formulated. The paper considers the problem associated with the elaboration of approaches to diagnosing early OA with clinical, laboratory, and modern instrumental examinations.